FACTORS LEADING TO CONVERSION OF LAPAROSCOPIC CHOLECYSTECTOMY TO OPEN CHOLECYSTECTOMY - Zubair, Muhammad; Nasir, Ammad Ud Din; Malik, Arsalan Sharif; Shaukat, Zeeshan; Naz, Faheem Ullah; Ramzan, Aman (Pakistan Armed Forces Medical Journal, 2022)
Objective: To evaluate the various factors leading to conversion of laparoscopic cholecystectomy to open cholecystectomy. Study Design: Comparative cross-sectional study. Place and Duration of Study: Pak Emirates Military Hospital Rawalpindi, from May 2020 to Sep 2021. Methodology: This study was conducted on 200 patients who underwent laparoscopic cholecystectomy for any benign pathology during the study period. Data was collected for all the patients who required conversion of surgical procedure from laparoscopic to open cholecystectomy. Demographic and clinical risk factors were associated with conversion of procedure in the study participants. Results: Out of 200 patients included in the final analysis 67 (33.5%) were male and 133 (66.5%) were female. Mean age of patients put who underwent laparoscopic surgery for benign gall bladder pathologies in our study was 43.46 ± 8.337 years. Gall stones were the commonest clinical condition for which laparoscopic cholecystectomy was done. Out of 26 (13%) patients underwent conversion of laparoscopic to open surgery. It was revealed that frozen Calots triangle (p-value-0.033), empyema gall bladder (p-value-0.018) and previous abdominal surgeries (p-value-0.013) were significantly related to conversion of laparoscopic to open surgery Conclusion: Conversion rate of laparoscopic to open surgery for cholecystectomy was high in our study population. Patients who had previous abdominal surgeries or presence of frozen Calots triangle and empyema gall bladder were more at risk of conversion of surgery.